Numerical simulation of autoclaved aerated concrete masonry wall subjected to close-in explosion and the structural damage assessment - Sheng Liu; Xiangyun Xu; Yilun Zhang; Bukui Zhou; Kezhi Yang (Scientific Reports, 2024)
Abstract In this study, we investigated the destructive effect of autoclaved aerated concrete (AAC) masonry walls subjected to close-in explosions. First, full-size refined finite-element models of the AAC masonry wall were established, and the accuracy of the models was verified by comparison with the test results. The destruction pattern and damage characteristics of the AAC wall were studied, and the effects of block size, wall thickness, mortar compressive strength, and explosion distance on the destruction degree of the AAC masonry walls were analyzed. The results showed that the destruction pattern of the AAC masonry wall subjected to close-in explosion manifested as punching damage in the middle of the wall. When the scaled distance remained unchanged, the punching damage area of the AAC masonry wall was positively correlated with the block size and negatively correlated with the wall thickness and mortar compressive strength. When the explosive equivalent remained unchanged and the explosion distance increased, the punching damage area first increased and then decreased. According to the damage mechanism of the AAC masonry wall, a calculation method for predicting the punching damage area of the AAC masonry wall was established, and the accuracy of this method was verified by comparing it with the numerical results. In addition, the damage criterion based on the punching damage area was established to determine the destruction levels of AAC masonry walls.